Americans in Tuscany : charity, compassion, and belonging - Trundle, Catherine (New directions in anthropology, 2014)
Since the time of the Grand Tour, the Italian region of Tuscany has sustained a highly visible American and Anglo migrant community. Today American women continue to migrate there, many in order to marry Italian men. Confronted with experiences of social exclusion, unfamiliar family relations, and new cultural terrain, many women struggle to build local lives. In the first ethnographic monograph of Americans in Italy, Catherine Trundle argues that charity and philanthropy are the central means by which many American women negotiate a sense of migrant belonging in Italy. This book traces women.